The nature of the alkaline phosphatases of bile - Price, C. P. (1972)
The main alkaline phosphatase isoenzymes of human bile have been purified by DEAE-cellulose chromatography. Characteristics of the isoenzymes, such as electrophoretic mobility before and after butanol extraction, Michaelis constant, and change in electrophoretic mobility following exposure to neuraminidase have been studied and compared with isoenzymes from other sources. The results show that the main alkaline phosphatase of bile is derived from the liver. It is present as a protein phosphatidylcholine complex.